2022
DOI: 10.1002/mp.15802
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid 2D/4D‐MRI methodology using simultaneous multislice imaging for radiotherapy guidance

Abstract: Purpose Respiratory motion management is important in abdominothoracic radiotherapy. Fast imaging of the tumor can facilitate multileaf collimator (MLC) tracking that allows for smaller treatment margins, while repeatedly imaging the full field‐of‐view is necessary for 4D dose accumulation. This study introduces a hybrid 2D/4D‐MRI methodology that can be used for simultaneous MLC tracking and dose accumulation on a 1.5 T Unity MR‐linac (Elekta AB, Stockholm, Sweden). Methods We developed a hybrid 2D/4D‐MRI met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Retrospective 4D-MRI can be achieved by continuously acquiring images with a respiratory signal recorded simultaneously and then assigning 2D slices to corresponding respiratory phases using internal or external surrogates. [187][188][189][190][191][192][193][194][195] Many studies have used fast MR sequences, including spoiled gradient echo and balanced steady-state free precession (bSSFP) sequences. For example, Cai et al developed a retrospective 4D-MRI technique that uses an image-based surrogate for respiratory motion.…”
Section: D-mrimentioning
confidence: 99%
“…Retrospective 4D-MRI can be achieved by continuously acquiring images with a respiratory signal recorded simultaneously and then assigning 2D slices to corresponding respiratory phases using internal or external surrogates. [187][188][189][190][191][192][193][194][195] Many studies have used fast MR sequences, including spoiled gradient echo and balanced steady-state free precession (bSSFP) sequences. For example, Cai et al developed a retrospective 4D-MRI technique that uses an image-based surrogate for respiratory motion.…”
Section: D-mrimentioning
confidence: 99%
“…A straightforward way to accelerate MRI is by undersampling the acquisition, violating the Shannon-Nyquist data sufficiency criterion, 25 and introducing image artifacts that may preclude accurate motion quantification. 24 Several techniques have been proposed to reconstruct high-quality MRI from undersampled acquisitions, such as parallel imaging, 26,27 simultaneous multi-slice acquisitions, [28][29][30] or compressed sensing. 31 Some algorithms have been specifically developed to reconstruct high-quality respiratory-resolved 4D-MRI by taking advantage of all spatio-temporal information in the images, such as XD-GRASP 32 or HDTV-MoCo.…”
Section: Introductionmentioning
confidence: 99%
“…In two follow up studies with the same motion predictor, they used Lujan motion and additionally one patient-derived motion trace to investigate MLC-tracking with VMAT plans 24 and with a hybrid 2D/4D-MRI methodology. 25 A limitation of all four studies is that either sinusoidal or a single patient-derived trace was used.…”
Section: Introductionmentioning
confidence: 99%
“…showed that an online LR can compensate the latency for the delivery of intensity modulated radiotherapy (IMRT) plans with MLC‐tracking to a phantom moving with Lujan motion (cos 4 ). In two follow up studies with the same motion predictor, they used Lujan motion and additionally one patient‐derived motion trace to investigate MLC‐tracking with VMAT plans 24 and with a hybrid 2D/4D‐MRI methodology 25 . A limitation of all four studies is that either sinusoidal or a single patient‐derived trace was used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation